Information literacy skills of Singapore secondary school students. - Ng, Song Beng. (2008)
In this study, the information literacy skills of the Singapore students in a secondary school were assessed and the readiness of its education system in the preparation of students for the information era was discussed. The results of this study showed that the typical subject relied upon adults to state questions and topics. They wandered from source to source without questioning which source would be most helpful. They lost track of most important information by leaving information as gathered. They reached a hasty conclusion by restating the decisions and solutions of others. Hence, although the Singapore students have been doing well in international academic competitions, the education system has to undergo a major overhaul in order to remain its relevance in the coming era.